2007
DOI: 10.1111/j.1559-1816.2007.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to Repeated Unpredictable Terror Attacks: Relationships Among Exposure, Posttraumatic Distress, Mood, and Intensity of Coping1

Abstract: We hypothesized that exposure to Type IV trauma (involving alteration in a person's basic relation to the environment), associated with prolonged terrorist threats, would impact posttraumatic distress and that exposure to terrorism would impact the intensity of coping. The relationships revealed by the data proved to be in line with this model. Our data suggested that the relationship of exposure and coping was not direct, but seemed to be mediated by posttraumatic distress, that demoralization at the height o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(6 citation statements)
references
References 50 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…These correlations are consistent with our theoretical model (i.e., that motivation for coping behaviors increases as terror-related distress and impairment increase) and recent studies on reactions to repeated acts of terrorism (e.g., Somer, Ruvio, Sever, & Soref, 2007). Positive Engagement was the only factor that was negatively related with the psychiatric outcomes (and the SF-36 subscales), implying protective capabilities, much like Acceptance in other studies (e.g., Somer et al, 2005;Somer et al, 2007). Unexpectedly, the relationships between the Fatalism subscale and the outcome variables were only small to moderate.…”
Section: Discussionsupporting
confidence: 91%
“…These correlations are consistent with our theoretical model (i.e., that motivation for coping behaviors increases as terror-related distress and impairment increase) and recent studies on reactions to repeated acts of terrorism (e.g., Somer, Ruvio, Sever, & Soref, 2007). Positive Engagement was the only factor that was negatively related with the psychiatric outcomes (and the SF-36 subscales), implying protective capabilities, much like Acceptance in other studies (e.g., Somer et al, 2005;Somer et al, 2007). Unexpectedly, the relationships between the Fatalism subscale and the outcome variables were only small to moderate.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the present research contributes to the growing psychological literature on responses to terrorism. Previous work on this topic has focused on stress and traumarelated responses in the aftermath of terrorism (e.g., Chu, Seery, Ence, Holman, & Silver, 2006;Somer, Ruvio, Sever, & Soref, 2007). Other work has investigated individuals' perceptions and emotions after a particular terrorist attack, such as 9/11 (Bergstrom & McCaul, 2004) or the London bombings (Bux & Coyne, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Geographic locations where terrorist attacks occur with regularity, for example, are also typically encumbered by other terrorist-related stressors, such as frequent reminders of the attack, likelihood of losing a loved one, personal injury, disruption in routine, and postdisaster stress in the community (Shalev, Tuval, Frenkiel-Fishman, Hadar, & Eth, 2006). Indeed, although studies of the September 11th attacks in New York consistently reported a positive association between geographic proximity and psychological distress (e.g., Adams & Boscarino, 2006; Boscarino, Adams, & Figley, 2004; Galea et al, 2002, 2003: Schuster et al, 2001; Silver, Holman, McIntosh, Poulin, & Gil-Rivas, 2002), population studies of terrorist attacks in Israel have often failed to reveal such associations (Bleich, Gelkopf, & Solomon, 2003; Bleich, Gelkopf, Melamed, & Solomon, 2006; Shalev et al, 2006; Somer, Ruvio, Sever, & Soref, 2007; Somer, Ruvio, Soref, & Sever, 2007).…”
Section: Disaster Outcome Depends On a Combination Of Risk And Resilimentioning
confidence: 99%